Pemodelan Volatilitas Indeks Harga Saham Sektoral di Indonesia - Yasir Maulana (Universitas Kuningan, 2022)
This study aims to determine the volatility model of the ten sectoral stock indexes on the Indonesia Stock Exchange accompanied by analysis of the influence of leverage and forecasting using the best model obtained. The method used is the ARCH model then extended to symmetric GARCH and asymmetric extension to GARCH, namely, GJR-GARCH and EGARCH. The results of the research that we have done on sectoral stock indexes show that the ten sectoral indices can be modeled for volatility. The best model for Consumer Goods, Miscellaneous, Infrastructure, and Property is GARCH(1,1). As for the Manufacturing, Trade, and Basic Industry sectors, the best model is GJR-GARCH(0,1,1) and for the Mining, Agriculture, and Finance sectors the best model is GJR-GARCH(1,1,1). Our analysis of the leverage effect found that several sectors showed a leverage effect, namely the manufacturing, mining, agriculture, trade, finance, and property sectors. This often reflects the fact that in the Indonesian stock market often volatility increases more quickly when there is bad news than volatility changes when there is good news for these sectoral indices.